The Student's First Clinical Experience: Anxiety and Phantasies Present in the Work with the Client and in the Supervision - Aguirre, Ana Maria Barros (2000)
In this paper we present facts and reflections based on the experience of over ten years in the supervision of the first psychological assessment performed by undergraduate students. Through clinical illustrations we state that the student's anxiety and phantasies - regarding both the work with the client and the supervision - play an important role in the clinical learning in a psychoanalytical approach.